Delivery of Hairpin RNAs and Small RNAs Into Woody and Herbaceous Plants by Trunk Injection and Petiole Absorption - Dalakouras, Athanasios; Jarausch, Wolfgang; Buchholz, Guenther; Bassler, Alexandra; Braun, Mario; Manthey, Thorsten; Krczal, Gabi; Wassenegger, Michael (Frontiers in Plant Science, 2018)
Since its discovery, RNA interference has been widely used in crop protection. Recently, transgene-free procedures that were based on exogenous application of RNA molecules having the capacity to trigger RNAi in planta have been reported. Yet, efficient delivery of such RNA molecules to plants and particularly to trees poses major technical challenges. Here, we describe simple methods for efficient delivery of hairpin RNAs (hpRNAs) and small interfering RNAs (siRNAs) to Malus domestica, Vitis vinifera, and Nicotiana benthamiana that are based on trunk injection and/or petiole absorption. The applied RNA molecules were efficiently taken up and systemically transported. In apical leaves, the RNA was already detectable 1 day post-application (dpa) and could be detected at least up to 10 dpa, depending on the method of application. Confocal microscopy revealed that the uptaken and systemically transported RNA molecules were strictly restricted to the xylem and apoplast which may illustrate why the applied hpRNAs were not processed into siRNAs by plant DICER-LIKE (DCL) endonucleases. These innovative methods may have great impact in pest management against chewing and/or xylem sap-feeding vectors and eukaryotic pathogens that reside in the xylem.